Mechanochemical feedback control of dynamin independent endocytosis modulates membrane tension in adherent cells. Issue 1 (December 2018) - Thottacherry, Joseph; Kosmalska, Anita; Kumar, Amit; Vishen, Amit; Elosegui-Artola, Alberto; Pradhan, Susav; Sharma, Sumit; Singh, Parvinder; Guadamillas, Marta; Chaudhary, Natasha; Vishwakarma, Ram; Trepat, Xavier; et al.
Abstract Plasma membrane tension regulates many key cellular processes. It is modulated by, and can modulate, membrane trafficking. However, the cellular pathway(s) involved in this interplay is poorly understood. Here we find that, among a number of endocytic processes operating simultaneously at the cell surface, a dynamin independent pathway, the CLIC/GEEC (CG) pathway, is rapidly and specifically upregulated upon a sudden reduction of tension. Moreover, inhibition (activation) of the CG pathway results in lower (higher) membrane tension. However, alteration in membrane tension does not directly modulate CG endocytosis. This requires vinculin, a mechano-transducer recruited to focal adhesion in adherent cells. Vinculin acts by controlling the levels of a key regulator of the CG pathway, GBF1, at the plasma membrane. Thus, the CG pathway directly regulates membrane tension and is in turn controlled via a mechano-chemical feedback inhibition, potentially leading to homeostatic regulation of membrane tension in adherent cells. Plasma membrane tension is an important factor that regulates many key cellular processes. Here authors show that a specific dynamin-independent endocytic pathway is modulated by changes in tension via the mechano-transducer vinculin.